Інтенсифікація охолодження соняшникової крупки на олієекстракційних заводах - Масліков, Михайло Олександрович; Масліков, Максим Михайлович; Бойко, Володимир Олександрович; Самійленко, Сергій Миколайович (My University, 2022)
Наведені результати дослідження ефективності охолодження соняшникової крупки у олієжировому виробництві. Проведено аналіз чинників, які впливають на інтенсивність охолодження сипучих крихких речовин. Представлені: методика розрахунку і комп’ютерна модель системи охолодження, результати обчислювального експерименту і їх аналіз. Розроблені методики розрахунку та конструкції засобів інтенсифікації охолодження: оребрення транспортерів крупки та повітряного душу для їх обдування. Наведені графіки залежності температури охолодженої крупки від способів охолодження та температури довкілля.

The results of the development of the sunflower oily cake cooling system at the oil production are presented in this article. The optimal oily cake temperature before extraction is 45 ‒ 55 °C. Its decrease leads to a decrease in the intensity of extraction and an increase in sunflower oil losses. Its increase leads to an increase in solvent losses due to evaporation. Cooling of the oily cake becomes relevant during global warming, especially noticeable in the south regions of Ukraine, where sunflowers are grown and processed. At domestic plants, the cooling of the oily cake usually occurs due to heat losses during its transportation for extraction. In world practice, heat exchangers are most often used for cooling bulk materials. However, significant grinding and removal of the material are observed in this case. The analysis of factors affecting the efficiency of cooling of bulk brittle materials is carried out, the advantages and disadvantages of using different cooling methods are revealed. A computer model of the cooling system has been developed, which allows determining the temperature of oily cake under different cooling conditions and the configuration of its transportation system. The results of the computational experiment carried out using the computer model are presented and analyzed. Graphs of the ambient temperature influence on the temperature of the cooled oily cake for different methods of its cooling are presented. On the basis of the computational experiment, the method of intensification of heat transferring from the oily cake to the ambient air with air blowing of the finned bottom of a part of the conveyors was chosen. For blowing under the finned conveyors, air boxes with slots are installed, which provide uniform in length air supply. The air is supplied by fans, exits through the slots at the same speed and blows the finned conveyors, improving heat removal from the fins. The methods of calculation and design of the finned conveyors and air showers for their blowing are developed.
Keywords: охолодження; екстракція; соняшникова крупка; інтенсивність; оребрення; транспортер; cooling; extraction; sunflower oily cake; intensity; fins; conveyor; кафедра теплоенергетики та холодильної техніки